UJI DAYA TERIMA SERTA KANDUNGAN GIZI YOGHURT DENGAN PEMANFAATAN SANTAN KELAPA (Cocos nucifera L) DAN BUAH KESEMEK (Dyospros kaki L) - mira maharani; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Coconut milk and persimmon fruit can be processed into a variety of food products one of them yoghurt that can contribute nutrients such as protein, calsium, vitamine A, and chemical content (pH and total acid) and microbiological content of lactic acid bacteria. Those components, which are essential for every human being. The purpose of this study was to knowed and analize the acceptability and nutrition community to the utilization of coconut milk and persimmon fruit as a raw material for making yoghurt. This research is an experimental research using complete randomized design. making yogurt with the addition of coconut milk and persimmon fruit with composition ratio (50%: 50%) and (70%: 30%). Research on acceptance test and yoghurt was conducted at Public Health Nutrition Laboratory, Faculty of Public Health, University of Sumatera Utara with 30 panelists, while nutrient analysis, chemistry and microbiology of yogurt was done at Food Science and Technology Laboratory, Faculty of Agriculture (FP). The results of organoleptic test to taste, aroma, texture and color of coconut milk yoghurt and persimmon fruit at a ratio of 50%: 50% protein contributed 6.41%, calcium 0,30%, vitamine A 0,31%, and water content 32 %, chemical content in yoghurt is pH 5.0 and total acid 1,2% and microbiology content is total lactic acid bacteria (BAL) 19x107 cfu/ml in 100 gram of material. While in the ratio of 70%: 30% protein contributed 2.6%, calcium 0.24%, vitamine A 0.28%, and moisture content 25%, chemical content in yogurt that is pH 4.0 and total acid 0, 7% and microbiological content of total lactic acid bacteria (BAL) 16x107 cfu / ml in 100 grams of material. Suggestions from this study is that people to use coconut milk and persimmon fruit in making yoghurt as alternative healthy snack, and drinking milk substitute for society (Elderly, teenager and toddler) who is unable to digest lactose (lactose intolerance). Keywords: yoghurt, coconut milk, persimmon fruit, organoleptic test, nutrition composition